Ablation behaviour of ultra-high temperature ceramic matrix composites: Role of MeSi2 addition. Issue 9 (August 2019) - Silvestroni, L.; Vinci, A.; Failla, S.; Zoli, L.; Rubio, V.; Binner, J.; Sciti, D.
Graphical abstract: Abstract: A new class of ZrB2 composites reinforced with 40 vol% C short fibers and containing 5 vol% SiC in combination with 5 vol% MoSi2, HfSi2 or WSi2 successfully withstood extreme conditions in a oxyacetylene torch. Different responses to the torch testing were recorded depending on which secondary phase was present; this was primarily a result of the final density which ranged between 83 and 94% of the theoretical value. The temperatures achieved on the surfaces of the samples tested also varied as a function of the residual porosity and ranged from 2080 to 2240 °C. HfSi2 additions offered the best performance and exceeded that of the baseline material that contained only SiC. It is believed that this was due to its ability to promote the elimination of porosity during densification and to the refractory nature of its oxide, HfO2 . In contrast, MoSi2 and WSi2 formed highly volatile oxides on the surface, which did not offer better protection than the ZrO2 -SiO2 scale that developed in the baseline.